Behavioral and neural outcomes of training manipulable verbs in aphasia: a proof-of-concept single subject experimental design - Faroqi-Shah, Yasmeen; Marshall, Kelly (Frontiers in Language Sciences, 2025)
IntroductionTraining outcomes for verb naming impairment in post-stroke aphasia are limited in their generalization to untrained verbs, and little is known about neuroplasticity associated with verb naming impairment. This is a proof-of-concept study that examined if manipulability (action involving a specific hand shape) is a conceptual feature of verbs.MethodsIndividual differences in verb naming outcomes and associated neuroplastic changes following training to produce manipulable verbs were compared using FMRI in a case series of two persons with post-stroke agrammatic aphasia who had a verb deficit.ResultsFollowing 12 sessions of training, trained verb naming improved while untrained manipulable and non-manipulable verb naming was unchanged. Functional magnetic resonance imaging of verb naming showed that correct verb naming recruited unlesioned areas of the verb network recruited by neurotypical speakers and a network of compensatory regions including the bilateral perisylvian and subcortical regions. The participant with a larger training effect size showed post-training upregulation in these compensatory regions while the participant with the modest effect size mostly showed a downregulation. In both participants, unlesioned regions of the neurotypical verb network showed a downregulation following verb training.DiscussionThe findings provided limited support for verb manipulability as a conceptual feature. The study also supported prior research on showing that a more effective response to intervention is associated with increased re-engagement of pre-existing networks associated with successful naming.